Kinetics and mechanism of the electroreduction of anodic layers produced on cadmium in alkaline solution containing sodium sulphide - Gassa, Liliana Mabel (1991)
The kinetics of the potentiostatic electroreduction of different anodic layers produced on cadmium in Na₂S containing alkaline solutions has been studied at 25°C. Two types of anodic layer were used: (i) layers produced in the potential range of CdS and Cd(OH)₂ stability, and (ii) layers predominantly composed of CdS. The electroreduction kinetics for both layers can be explained reasonably well throughout the nucleation and growth processes under diffusion control.